Anaesthesia and handling stress effects on pigmentation and monoamines in Arctic charr - Backström, Tobias; Heynen, Martina; Brännäs, Eva; Nilsson, Jan; Winberg, Svante; Magnhagen, Carin (Environmental Biology of Fishes, 2017)
Stress responsiveness differs between individuals and is often categorized into different stress coping styles. Using these stress coping styles for selection in fish farming could be beneficial, since stress is one main factor affecting welfare. In Arctic charr (Salvelinus alpinus) carotenoid pigmentation is associated with stress responsiveness and stress coping styles. Thus this could be an important tool to use for selection of stress resilient charr. However, anaesthetics seem to affect carotenoid pigmentation, and it would be better if the method for selection could be implemented during normal maintenance, which usually includes anaesthetics. Therefore, this study investigated how the use of anaesthetics affected carotenoid pigmentation, i.e. number of spots, over time compared to no-anaesthetic treatment. Additionally, the stress indicators monoamines and glucocorticoids were investigated. The results indicate that the anaesthetic MS-222 affects number of spots on the right side. This anaesthetic also increased dopaminergic activity in the telencephalon. Both brain dopaminergic and serotonergic activity was associated with spottiness. Further, behaviour during anaesthetization was associated with spots on the left side, but not the right side. Repetition of the same treatment seemed to affect spot numbers on the right side. In conclusion, this study shows that inducing stress in charr affects the carotenoid spots. Thus, it is possible to use anaesthetics when evaluating spottiness although careful planning is needed.